A 1H‐NMR spectroscopic method for the analysis of thermolabile chemical markers from the essential oil of black turmeric (Curcuma caesia) rhizome: application in post‐harvest analysis. Issue 1 (26th June 2019) - Mahanta, Bhaskar Protim; Sut, Dristi; Kemprai, Phirose; Paw, Manabi; Lal, Mohan; Haldar, Saikat
Abstract: Introduction: Curcuma caesia (black turmeric), an essential oil‐bearing rhizomatous herb has been a part of ethnomedicinal practices in India and southeast Asian countries since ancient time. Oleochemical profile of black turmeric has been investigated previously by gas chromatography coupled to mass spectrometry (GC–MS) technique from different geographical regions showing a large variation in the identity as well as abundance of the constituents. Objectives: To develop an analytical method for the reliable analysis of essential oil from black turmeric rhizome through identified chemical markers and to show the credibility of the developed method on real samples. Methods: The essential oil of black turmeric was analysed through proton nuclear magnetic resonance ( 1 H‐NMR) based method using an internal standard. Results: Four thermolabile sesquiterpene markers were unambiguously identified from the essential oil of black turmeric rhizome. GC–MS based analysis produced an erroneous identification of the constituents. A standardised 1 H‐NMR spectroscopy based method was developed for the qualitative and quantitative analysis of the identified chemical markers. The developed method was further utilised for analysing the variation in oleochemical profile across multiple batches of harvest and the rhizomes subjected to different post‐harvest storage or drying conditions. Conclusion: The identified marker molecules and developed 1 H ‐NMR spectroscopic method might prove to be a useful tool for the analysis of essential oil and quality control of this endangered crop material. Also, the present study provided information on the preferred drying and storage condition of black turmeric rhizome prior to the extraction of essential oil. Abstract : Curcuma caesia (black turmeric), an essential oil bearing rhizomatous herb has been a part of ethnomedicinal practices in Asian countries since ancient time. A 1 H‐NMR (Nuclear Magnetic Resonance) spectroscopy based method was developed for the qualitative and quantitative analysis of the essential oil from black turmeric rhizome using four sesquiterpenoid chemical markers. The developed method was utilized for analyzing the essential oil from multiple batches of harvest and the rhizome subjected to different post‐harvest storage or drying conditions.